Predation, individual variability and vertebrate population dynamics. - Pettorelli, N; Coulson, T; Durant, S; Gaillard, J (2011)
Both predation and individual variation in life history traits influence population dynamics. Recent results from laboratory predator-prey systems suggest that differences between individuals can also influence predator-prey dynamics when different genotypes experience different predation-associated mortalities. Despite the growing number of studies in this field, there is no synthesis identifying the overall importance of the interactions between predation and individual heterogeneity and their role in shaping the dynamics of free-ranging populations of vertebrates. We aim to fill this gap with a review that examines how individual variability in prey susceptibility, in predation costs, in predator selectivity, and in predatory performance, might influence prey population dynamics. Based on this review, it is clear that (1) predation risk and costs experienced by free-ranging prey are associated with their phenotypic attributes, (2) many generalist predator populations consist of individual specialists with part of the specialization associated with their phenotypes, and (3) a complete understanding of the population dynamic consequences of predation may require information on individual variability in prey selection and prey vulnerability. Altogether, this work (1) highlights the importance of maintaining long-term, detailed studies of individuals of both predators and prey in contrasting ecological conditions, and (2) advocates for a better use of available information to account for interactive effects between predators and their prey when modelling prey population dynamics.